PENGARUH CITRA MEREK DAN HARGA TERHADAP MINAT BELI PRODUK JILBAB SEGI EMPAT ELZATTA (SURVEI PADA KONSUMEN GRAI ELZATTA LAHAT) (Ekonomika, 2022)
The title of this research is "The Influence of Brand Image and Price on Purchase Intention of Elzatta's Quadrangle Hijab Products (Survey on Grai Elzatta Lahat Consumers)". The purpose of this study was to determine and analyze the effect of facilities on customer satisfaction. To find out, analyze and prove the effect of brand image on buying interest in Elzatta's rectangular hijab products on Grai Elzatta Lahat's consumers, to find out, analyze and prove the effect of price on buying interest in facet hijab products. four Elzatta for Grai Elzatta Lahat Consumers and to find out, analyze and prove the effect of brand image and price on the purchase interest of Elzatta's rectangular hijab products on Grai Elzatta Lahat's consumers. Primary data in this study were obtained by distributing questionnaires to 86 consumers of Grai Elzatta Lahat. The data analysis technique used was the SPSS version 23.0 application, using data testing and statistical testing. From the results of data analysis on the variables studied, namely brand image and price, it shows that there is an influence on the buying interest of Elzatta's rectangular headscarves for Grai Elzatta Lahat consumers simultaneously and partially.